SOCIAL THEOLOGY: RE-ACTUALIZING CULTURAL VALUES INTO SOCIETY TRANSFORMATION - Hardi Putra Wirman; Nunu Burhanuddin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
This paper discusses the issue of theology that is indebted to sciences and technology. Technology, even though imposes a negative impact on theology particulary to those whose faith is still unstable, has strengthened Moslem’s belief and does not become a threat. How technology reinforces the faith of Moslem is strongly related to the agenda of reactualization through the praxis activities. The mode of social life should be put on the basis of social transformation in accordance with needs and challenges. The tranformation is closely tied to the development with race structure or human consciousness with the environment. The modification of human life in order to achieve such transformation can be actualized through four basic cultural structures: ethical constitution, esthetic, work orientation and the knowledge of technology. The writer concludes that four elements mentioned above determines the success of Islamic civilization for the future life.